1958
DOI: 10.1136/bmj.2.5095.528
|View full text |Cite
|
Sign up to set email alerts
|

Some Aetiological Aspects of Coronary Heart Disease

Abstract: JBmO of the circumstances which depress the rate of clearance of citrate from the plasma are present, by having available blood collected without the use of citrate. Heparin may be used-though this is often undesirable, particularly in vascular surgery-or blood may be collected over an ionexchange resin (Walter, 1950). The use of commercial packs for the latter purpose has been satisfactory in our hands, though they are expensive and the blood may be safely stored for only about 10 days. SummaryHigh plasma cit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

1959
1959
1986
1986

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…This finding would seem to run parallel with the clinical observations from this institution (Malhotra and Pathania, 1958) that the highest incidence of coronary heart disease is also in the sixth decade.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This finding would seem to run parallel with the clinical observations from this institution (Malhotra and Pathania, 1958) that the highest incidence of coronary heart disease is also in the sixth decade.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that atheroma and coronary heart disease are very uncommon in Asiatics as compared with Europeans (Arnott, 1954;Lancet, 1955). So far as clinical evidence is concerned, it was reported by one of us (Malhotra and Pathania, 1958) that not only is coronary heart disease not uncommon in this part of India but its general pattern also broadly conforms to the descriptions given by Western authors. The present investigation was conducted in order to determine the prevalence of coronary atherosclerosis in the general population in this extreme northern part of India.…”
supporting
confidence: 79%
“…These figures do not support the view that coronary disease develops at a relatively earlier age among diabetics (Friedberg, 1956). In the present series coronary disease was 1.7 times commoner in males than in females (Table ll), compared with a figure of 6.7 times in Malhotra and Pathania's (1958) at an ele=to-Electrocardiographic Findings.-The incidence of various electrocardiographic abnormalities in the coronary and hypertensive diabetics is shown in Table VII. Evidence of recent or old myocardial infarction was shown in 25 (32.9%) cases in the coronary group-20 (8.1%) were males and 5 (4.9%) females-a maleto-female incidence ratio of 1.7: 1, which is the same as for the whole group of 76 cases.…”
Section: Coronary Heart Diseasesupporting
confidence: 43%
“…Only one patient-an obese man aged 38-who had been diabetic for eight years was under 40. A comparison of the age distribution of coronary disease in diabetics with that in an unselected series of cases (Malhotra and Pathania, 1958) is given in Table IV. These figures do not support the view that coronary disease develops at a relatively earlier age among diabetics (Friedberg, 1956).…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…Except for two women who refused to cooperate with the present study, the entire population above the age of 30 years consisting of 845 men and 480 women was covered in Sector 16, and then the study was extended to Sector 22 where not a single person refused examination. In this sector also, with a population of the relevant age groups of over 3,000, contiguous households and shops were examined starting with the shopping area.…”
Section: Selection Of Samplementioning
confidence: 99%